Creating decent work for all - Reuben, Shanya (PINS-Psychology in Society, 2025)
Carr, S C, MacLachlan, M & Furnham, A (eds) (2012) Humanitarian work psychology. Houndmills: Palgrave Macmillan. ISBN 978-0-230-27545-4. Pages xxiii + 359 Up until very recently, psychology’s contribution to humanitarian work has been insufficient and modest. Humanitarian work psychology presents a new speciality within the field of Industrial and Organisational (I/O) psychology that focuses on humanitarian work. The book provides compelling arguments for organising humanitarian work to meet humanitarian ends. Humanitarian work psychology is the application of I/O psychology to humanitarian issues with a specific focus on developing a psychology that promotes humanitarian work. From both an ethical and practical perspective, humanitarian work psychology promotes humanistic as well as humanitarian ends including the United Nations Millennium Development Goal of reducing world poverty by 50% by 2015 (Annan, 2000). Humanitarian work psychology is in every way invested in the promotion, creation and maintenance of decent work for all.